Penguatan Pendidikan Karakter melalui Cerita Rakyat Berbasis Media Flibook untuk Siswa Sekolah Dasar - Musaddad, Reyno Bustami Musaddad; Vera Risti Desvani; Indriana Dwi Saputri; Lutfha Nugraheni (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to describe the use of learning media in the form of digital comics based on fable stories as a means to improve the speaking skills of elementary school students. The background of this study is the low interest of students in speaking and the limited learning media that are interesting and in accordance with their age characteristics. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, questionnaires, and speaking skills tests. The subjects in this research are fourth grade students of SDN Margasari 01 Balikpapan City. The results show that the use of digital comic media based on fable stories can increase students' courage in speaking, expand their vocabularies, and help students construct sentences more coherently and communicatively. Teachers and students also give positive responses to the media used because it is considered interesting, contextual, and in accordance with the learning needs. Thus, digital comic media based on fable stories can be an innovative alternative in learning Indonesian in elementary schools to improve the speaking skills of elementary school students.